Mercury Contamination in Limboto Lake - Sri Nawangsari Niode; Hasim Hasim; Faizal Kasim (Faculty of Fishery and Marine Sciences - Universitas Negeri Gorontalo, 2020)
The purpose of this study was to determine the content of heavy metal mercury (Hg) in Limboto Lake waters. Sampling was conducted at 5 stations, namely Station 1 (estuary of the Biyonga River), Station 2 (estuary of the Alopohu River), Station 3 (floating net cages), Station 4 (non KJA) and Station. 5 (Outlet at Sungai Tapodu). Sampling both at the surface and the bottom of the water is only done once. Analysis of the content of mercury (Hg) was carried out at the Gorontalo Province Fishery Product Quality Development and Testing Laboratory (LPPMHP). The results showed that the mercury (Hg) content in Limboto Lake waters for Station 1 in the water samples taken was 0.027 mg / L, the sediment samples were 13.61 mg / L, for Station 2 namely water sample 0.013 mg / L and sediment sample 12.27 mg / L, Station 3, namely water sample 0.003 mg / L sediment sample 8.35 mg / L, while Station 4, namely water sample 0.0142 mg / L sediment sample 7.71 mg / L and for Station 5, water sample 0.016 mg / L sediment sample 6.79 mg / L. The condition of the heavy metal content of mercury (Hg), based on water quality standards of 0.001 mg / L and sediment quality standards of 0.2 mg / L, on average, has exceed the maximum limit, namely the level of mercury in the water is 0.0146 mg / L (> 0.001 mg / L) and the mercury level in the sediment was 9,746 mg / L (0.2 mg / L). Keywords: mercuri (Hg); water; sediment; Limboto